With Gratitude from RHiME: Reviewers 2022 - RHiME, Editor (Research and Humanities in Medical Education, 2022)
The Editorial Board of RHiME would like to thank the following reviewers for their outstanding contribution to the work of the journal. Without their dedication and the time they devoted to the evaluation of submissions made to RHiME, it would have been impossible to maintain the standard of the journal. Amir Maroof Khan Jagriti Gangopadhyay Jaikumar B Contractor Jessica Oudenampsen Navjeevan Singh Radhika Kannan Rajat Thawani Sambit Dash Satendra Singh Swathi Poornima Chandaka Swati Satish Joshi Upreet Dhaliwal